Kapasitas Lentur Balok Pada Beton Bertulang dengan Agregat Lokal dari Sungai Babulu Malaka, Nusa Tenggara Timur - Bianco , Ricardo Justino; Rasidi , Nawir; Wijaya , Handika Setya; Ningrum, Diana (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Sand and crushed stone from the Babulu River in Malacca Regency is one of the materials that is often used by the local community as an aggregate for concrete construction, as a construction material the aggregate must meet technical requirements. The research method used was experimental with cylindrical samples measuring 15 cm x 30 cm and beams measuring 8 cm x 12 cm x 120 cm. The aggregate variations used were 0%, 25%, 50%, 75%, and 100%. Data were analyzed by assessing physical properties such as sieve analysis, silt content, moisture content, and specific gravity of aggregates. Further testing was carried out to test the compressive strength of concrete, to test the bending strength of the beam, and the deflection that occurs in the beam. The results showed that the sand and crushed stone material from Babulu River had a fineness modulus of 3.61%, while that of Malang Regency was 2.63%. Meanwhile, for coarse aggregate, the fineness modulus gradation of Babulu River is 4.06%, while that of Malang Regency is 4.43%. The use of the 50% variation of aggregate material from the Babulu River in the concrete mix produced a fairly good average compressive strength value. At 28 days of age, concrete using material from the Babulu River achieved an average compressive strength of 16.26 MPa. Reinforced concrete beams using materials from the Babulu River had an average flexural load-bearing capacity of 1,800 kg and an average deflection of 5.16 mm.